Do Economic Preferences of Children Predict Behavior? - Laura Breitkopf; Shyamal Chowdhury; Shambhavi Priyam; Hannah Schildberg-Hörisch; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2024)
We use novel data on nearly 6,000 children and adolescents aged 6 to 16 that combine incen-tivized measures of social, time, and risk preferences with rich information on child behavior and family environment to study whether children's economic preferences predict their behavior. Re-sults from standard regression specifications demonstrate the predictive power of children's pref-erences for their prosociality, educational achievement, risky behaviors, emotional health, and behavioral problems. In a second step, we add information on a family's socio-economic status, family structure, religion, parental preferences and IQ, and parenting style to capture household environment. As a result, the predictive power of preferences for behavior attenuates. We discuss implications of our findings for research on the formation of children's preferences and behavior.
Keywords: C91; D01; 330; social preferences; time preferences; risk preferences; experiments with children; origins of preferences; human capital; behavior